PENGARUH AKUNTANSI AKUNTABILITAS, SASARAN ORGANISASI DAN KETERLIBATAN ANGGARAN TERHADAP EFEKTIVITAS MANAJERIAL KANTOR PERWAKILAN BANK INDONESIA SOLO - Ariyanto Sahid; Maya Widyana Dewi; Rukmini Rukmini (Jurnal Ilmiah Akuntansi, 2025)
The purpose of this study was to determine the effect of accountability accounting, organizational goals and budget participation on managerial performance of the Solo Representative Office of Bank Indonesia. This study uses data collection methods with questionnaires. The population used is Bank Indonesia Solo employees from all units (Rupiah Money Processing Unit, SP Policy Implementation Unit and SP PUR Supervision, Internal Management Unit and Kekda Implementation Unit). Data analysis methods with descriptive data of respondents, data quality test (validity test, reliability), classical assumption test (normality test, multicollinearity test, heteroscedaticity test) and for hypothesis testing using multiple linear analysis, F test, t test and coefficient of determination test. In this study obtained a sample of 65 people. Based on the test results it can be concluded that Accountability Accounting affects Managerial Performance, Organizational Goals affect Managerial Performance and Budget Participation has no effect on Managerial Performance.